Factors Associated with Exclusive Breastfeeding of Rajavithi Hospital Staff - Plewma, Phawinee; Sangpithak, Waranya (Journal of The Department of Medical Services, 2022)
Background: Breastfeeding provides the best nutrients for infants. Thus, infants should be exclusivelybreastfed during their first 6 months, according to the recommendation by the World Health Organization and UNICEF. After that, they should both receive age-related supplements and be breastfed until they are 2 years old. At the present time, the rate of breastfeeding tends to decrease. A study from the Department of Health has stated that there is only 23.6 percent of mothers that breastfeed their children. However, breastfeeding is found to be fundamental for children’s physical, mental, and emotional growth. Objective: This study aims to examine factors related to the success of breastfeeding of staff at Rajavithi Hospital. Method: This descriptive research collected data from female staff working at Rajavithi hospital with children aged from 6 months to 4 years old. In which the staff brought their children to the breastfeeding clinic, the day-care center, or the well-being development center at Rajavithi Hospital. A questionnaire with a rating scale was used as a tool for gathering data. Frequency, percentage, mean, standard deviation, and Chi-Square analysis were used as required parameters. Result: The success rate of breastfeeding was 49.0%. Factors related to the success of breastfeeding were the attitude toward breastfeeding, the experience of breastfeeding, and the service of the breastfeeding clinic, which provided statistical significance at p-value .05. Conclusion: The attitude toward breastfeeding, the experience of breastfeeding, and the service of the breastfeeding clinic are factors associated with the success of breastfeeding